Effects of yogurt and bifidobacteria supplementation on the colonic microbiota in lactose-intolerant subjects - He, T; Priebe, M.G; Zhong, Y; Huang, C; Harmsen, H.J.M; Raangs, G.C; Antoine, J.-M; Welling, G.W; Vonk, R.J (Journal of applied microbiology, 2008)
Colonic metabolism of lactose may play a role in lactose intolerance. We investigated whether a 2-week supplementation of Bifidobacterium longum (in capsules) and a yogurt enriched with Bifidobacterium animalis could modify the composition and metabolic activities of the colonic microbiota in 11 Chinese lactose-intolerant subjects. The numbers of total cells, total bacteria and the Eubacterium rectale/Clostridium coccoides group in faeces as measured with fluorescent in situ hybridization and the faecal β-galactosidase activity increased significantly during supplementation. The number of Bifidobacterium showed a tendency to increase during and after supplementation. With PCR-denaturing gradient gel electrophoresis, in subjects in which B. animalis and B. longum were not detected before supplementation, both strains were present in faeces during supplementation, but disappeared after supplementation. The degree of lactose digestion in the small intestine and the oro-caecal transit time were not different before and after supplementation, whereas symptom scores after lactose challenge decreased after supplementation. The results suggest that supplementation modifies the amount and metabolic activities of the colonic microbiota and alleviates symptoms in lactose-intolerant subjects. The changes in the colonic microbiota might be among the factors modified by the supplementation which lead to the alleviation of lactose intolerance. This study provides evidence for the possibility of managing lactose intolerance with dietary lactose (yogurt) and probiotics via modulating the colonic microbiota.